2022
DOI: 10.3390/cells11071149
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Functions and the Mechanisms of Long Non-Coding RNAs in Cervical Cancer

Abstract: Cervical cancer is one of the leading causes of death in gynecology cancer worldwide. High-risk human papillomaviruses (HPVs) are the major etiological agents for cervical cancer. Still, other factors also contribute to cervical cancer development because these cancers commonly arise decades after initial exposure to HPV. So far, the molecular mechanisms underlying the pathogenesis of cervical cancer are still quite limited, and a knowledge gap needs to be filled to help develop novel strategies that will ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 160 publications
0
9
0
Order By: Relevance
“…LncRNAs has been widely reported to participate in the development and progression of various cancers ( Yang and Al-Hendy, 2022 ). However, there was no cuproptosis-related lncRNA reported up to now.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs has been widely reported to participate in the development and progression of various cancers ( Yang and Al-Hendy, 2022 ). However, there was no cuproptosis-related lncRNA reported up to now.…”
Section: Discussionmentioning
confidence: 99%
“…(Winkle et al, 2021). LncRNAs were found to play an important role in the cellular biological behavior of CC through various mechanisms, and these molecules may be effective molecular targets in the treatment of CC (Yang and Al-Hendy, 2022). Thus, in the future, we should study the potential interactions between lncRNAs and the activity of copper to identify potential prognostic markers and to find the predicted and therapeutic targets of CC.…”
Section: Discussionmentioning
confidence: 99%
“…The central mechanism of signal transduction by the TGF-β family receptors follows a well-characterized process of interactions and receptor-mediated phosphorylation. Upon ligand binding and the following cascade steps, the trimeric complex (SMAD2, 3, 4) translocates into the nucleus and associates with high-affinity DNA binding transcription factors and chromatin remodeling proteins, thereby positively or negatively regulating the transcription of the TGF-β-responsive genes [ 30 ]. Numerous studies demonstrated that TGF-β signaling plays an important role in the pathogenesis of UFs.…”
Section: Extracellular Matrix and Regulation In Uterine Fibroidsmentioning
confidence: 99%